IMPLEMENTASI PERATURAN DAERAH KOTA METRO NOMOR 8 TAHUN 2015 TENTANG PENGELOLAAN SAMPAH DALAM MENINGKATKAN KEBERSIHAN DI KOTA METRO - Amallia, Neysa (JURNAL SOSIAL DAN HUMANIS SAINS, 2017)
Waste management in Metro City refers to City Regional Regulation No. 8 of 2015 on Waste Management is a systematic, comprehensive and continuous activity which includes waste reduction and handling. Garbage management and hygiene issues in Metro City are often the main complaints of pedestrians and too many riders there is garbage in places of tourism and markets. Metro City has not been able to do waste management properly. In addition, the participation of Metro City community on the environment is still fairly low. This is evident in the behavior of people who still throw garbage carelessly. The purpose of this research is to know and analyze waste management in Metro City in improving cleanliness and to know and analyze public participation in waste management in Metro City. The research method used in this research is descriptive by using qualitative analysis. Technique of collecting data of this research through interview technique to subject of information and documentation. The results show that waste management in improving hygiene in Metro City has not been all running in accordance with local regulations. In determining the target of restriction of waste reduction still has not been determined by City Planning Department and Tourism City Metro. For garbage collection and transportation activities have their own guarantor. Then community participation in waste management in Metro City has not fully complied with Local Regulation No. 8 Year 2015 on Waste Management. The community has not complied with the rules of waste disposal which should not be disposed of in temporary shelters but directly disposed of in landfills.